Prediction of Rashba Effect on Two-dimensional MX Monochalcogenides (M = Ge, Sn and X = S, Se, Te) with Buckled Square Lattice - Ibnu Jihad; Juhri Hendrawan; Adam Sukma Putra; Kuwat Triyana; Moh. Adhib Ulil Absor (Indonesian Journal of Chemistry, 2020)
The Rashba splitting are found in the buckled square lattice. Here, by applying fully relativistic density-functional theory (DFT) calculation, we confirm the existence of the Rashba splitting in the conduction band minimum of various two-dimensional MX monochalcogenides (M = Ge, Sn and X = S, Se, Te) exhibiting a pair inplane Rashba rotation of the spin textures. A strong correlation has also been found between the size of the Rashba parameter and the atomic number of chalcogen atom for Γ and M point in the first Brillouin zone. Our investigation clarifies that the buckled square lattice are promising for inducing the substantial Rashba splitting suggesting that the present system is promising for spintronics device.